POLITICAL WILL PEMERINTAH KABUPATEN SIAK DALAM PENGALIHAN FUNGSI LAHAN TAHUN 2020-2021 - Olivia Andreani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Political Will or political will which is defined as the "leader's intention" to do things that are deemed necessary for the common interest in the long term. Political will is also interpreted if the state has the will, but of course it must be supported by the people. While land conversion is a change in the function of part or all of the land area from its original function (according to plan) to another function. This research discusses the political will carried out by the Siak Regency Government in transferring land functions in 2020-2021. There have been many changes in land use that occurred in Siak Regency, where at first the land was rice farming, then turned into oil palm plantations and returned to rice farming. political will, namely government initiatives, policy/program options, mobilization of parties, public commitment and resource allocation, business continuity, learning and adaptation. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then, the location of this research was conducted in Siak Regency. The results of the study explain that the political will carried out by the Siak Regency Government by making legal aid products, namely Regional Regulation No. 02 of 2014 concerning the protection of sustainable food agricultural land as a derivative of Law No. 41 of 2009. The Regional Regulation is socialized to the community by providing assistance for people who want to convert their land into rice farming. Keywords: Political will, Land conversion, Rice farming